Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Immunogenicity and post-challenge virological outcomes of a multivalent subunit vaccine in sheep challenged with cytopathic BVDV-1a - Zhiran Shao; Jing Yuan; Yuhao Li; Lu Xiao; Rongrong Ni; Yinuo Li; Yalin Gao; Zeyao Wang; Yuting Zhang; Aodi Wu; Maoyuan Gu; Junyuan Li; et al. (Veterinary Microbiology, 2026)

Ultrasound-microwave synergistic treatment modulates highland barley dough structure and bread quality characteristics - Xiaolu Wu; Liping Fu; Xinyi Chen; Sizhe You; Wenhui Zhang; Liangfeng Ma; Qisen Xiang; Yuting Tian; Yingting Zhao (Food Research International, 2026)

Occurrence and risk assessment of benzotriazole UV stabilizers in a major drinking water reservoir by target, suspect, and nontarget screening analysis - Yuting Dong; Rifu You; Mingliang Liu; Xueqin Wei; Jie Fu; Guohua Zhu; Guogan Peng; Kai Huang; Bao Zhu; Pengyang Li; Haiyan Zhang; Aiqian Zhang; et al. (Water Research, 2026)

The content, bio-accessibility and in vitro bioavailability of lead species in various seafood samples collected from Fujian, China - Siyi liu; Ying Peng; Yuting Yang; Wenchao Lv; Jingguang Li; FengFu Fu; Yue Lin (Journal of Hazardous Materials, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Retraction notice to “Influence of the morphological change in natural Asian dust during transport: A modeling study for a typical dust event over northern China” [Sci. Total Environ. 739 (2020) 139791] - Yu Tian; Zhe Wang; Xiaole Pan; Jie Li; Ting Yang; Dawei Wang; Xiaoyong Liu; Hang Liu; Yuting Zhang; Shandong Lei; Yele Sun; Pingqing Fu; et al. (Science of The Total Environment, 2026)

Molecular orchestration of highland barley starch-β-glucan complexes under extrusion thermomechanics: linking hierarchical structure to digestive resistance - Liping Fu; Yingting Zhao; Xinyi Chen; Lujie Cheng; Can Zhao; Yang Liu; Yixin Zheng; Yingying Yan; Qisen Xiang; Wenhui Zhang; Yuting Tian (Food Research International, 2026)

Ovarian Development in Channa argus var.: Joint Mediation by Melatonin, the cAMP Signaling Pathway, and the PI3K-Akt Signaling Pathway in Response to Photoperiod - Hejiao Li; Yuting Duan; Rongrong Liao; Yinhua Zhou; Jian Su; Xinyu Liu; Tinghui Xia; Yixin Luan; Mei Peng; Suxing Fu; Benhe Zeng; Luo Lei; et al. (Marine Biotechnology, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Partial debranching and microwave treatment stabilize amylopectin-flavor interactions for better tsampa processing outcomes - Xinyi Chen; Liping Fu; Ye Xu; Lujie Cheng; Zijian Huang; Wenhui Zhang; Qisen Xiang; Yang Liu; Yuting Tian; Yingting Zhao (Carbohydrate Polymers, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

A review of machine learning applications in soil heavy-metal remediation: material design, process optimization, and future challenges - Minsheng Fu; Zhipeng Tang; Yuting Liu; Yumeng Zhou; Chenyang Zhang (Environmental Geochemistry and Health, 2026)

Highly amphiphilicity-tailorable pineapple-like janus nanozymes with superior kinematic locomotion facilitates biphasic chemiluminescence analysis - Xin Jiang; Wan Wei; Yueming Zhao; Lingli Zhang; Wenwen Wang; Yuting Zhao; Zhongjie Zhu; Zhifeng Fu; Chengzhou Zhu; Hui Ouyang (Analytica Chimica Acta, 2026)

Phase-modulated engineering of oxygen-doped molybdenum disulfide for boosting visible light-driven photocatalytic tetracycline degradation - Ze Yuan; Chenghao Li; Nan Feng; Xinping Fu; Yuting Ning; Wei Yao; Lepu Ci; Jun Cui (Journal of Environmental Chemical Engineering, 2026)

Ubiquitous and remarkable tire-derived chemicals (TDCs) contamination in road-related environmental receptors across the Tibetan plateau - Qianyuan Yang; Wei Zhou; Qiangying Zhang; Wenxiao Pan; Xiaomei Cui; Yuting Dong; Jifu Liu; Chuanlong Zhang; Duo Bu; Aiqian Zhang; Jianjie Fu; Guibin Jiang (Environmental Research, 2026)

Nitrogen and Sulfur Deposition Contributes to Soil Acidity Variation Under Different Land use Patterns Over Decade in a Subtropical Small Watershed - Hanchen Wu; Xiaobin Guo; Li Tang; Yuting Dai; Wenqian Jiang; Haoyu Fu; Pei Luo; Jianlin Shen; Jinshui Wu (Water, Air, & Soil Pollution, 2026)

Optimizing Pistacia lentiscus (mastic tree) food and healthcare applications: phytochemical composition, extraction methods, quality control, and novel delivery systems - Mohamed A. Anwar; Yuting Fu; Haroun Khan; Mohamed A. Farag (Phytochemistry Reviews, 2026)
Pistacia lentiscus , from the Anacardiaceae family, is native to the Mediterranean region and best known for its aromatic resin, Chios mastic gum (CMG), which is exclusively produced on Chios Island, Greece. While the gum is the tree’s primary commercial product, various extracts from different P. lentiscus organs also hold potential applications due to their rich chemical profiles. This review assesses strategies to optimize the utilization of P. lentiscus products, not only the oleogum, in food and healthcare products. First, we review the phytochemical composition and environmental factors affecting this composition, highlighting conditions that maximize yield for different uses and applications. Additionally, various extraction techniques are reviewed, including solvent, ultrasonic-assisted, microwave-assisted, and supercritical fluid extraction methods, to identify the most effective methods. Authentication and quality control aspects, particularly for CMG, are compared, besides highlighting recent advances in novel delivery systems, i.e., liposomes, that are used to enhance the bioavailability of CMG key phytoconstituents. Graphical abstract

Effects of geomorphic drivers and nutrient enrichment on periphyton nutrient retention in an urban stream: A multi-habitat comparative experiment - Ruzhong Li; Yuting Wang; Yang Fu; Chenyang Han; Lingxiao Qin (Limnologica, 2026)

The discovery of natural-product inhibitors targeting white spot syndrome virus dUTPase (WSV112) through virtual screening and bioassays - Shangming Ran; Yuting Fu; Xiaolong Xue; Yueling Zhang; Defu Yao; Guanghui Chen (Aquaculture, 2026)

Metabolomic investigation of flavor and metabolite evolutions in the submerged fermentation of miiuy croaker (Miichthys miiuy) surimi induced by Monascus purpureus - Wenjia He; Min Wang; Tao Zhou; Sufang Fu; Kang Chen; Yuting Ding; Xuxia Zhou (Food Chemistry, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

Granulated organic amendments enhance soil organic carbon sequestration and saturation by modulating functional pools in infertile paddy soils - Yan Li; Lijia Liu; Yingnan Xian; Haoyu Fu; Li Tang; Yuting Dai; Wei Gao; Yan Li; Shoulong Liu; Junjian Li; Xiaobin Guo; Jinshui Wu (Plant and Soil, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

Smartphone app-enabled dual-mode fluorescence and colorimetric portable sensors using RB@BSA-AuNRs for quality identification of plant-derived products - Hengye Chen; Xueqing Zeng; Guanghua Lei; Yun Huang; Wanjun Long; Wei Lan; Yuting Guan; Haiyan Fu (Food Research International, 2026)

A centrifugal speed-based method for controlling debranched products of highland barley amylopectin distribution and isolating long-branched chains - Xinyi Chen; Can Zhao; Yang Liu; Liping Fu; Wenhui Zhang; Qisen Xiang; Yuting Tian; Yingting Zhao (Food Hydrocolloids, 2026)

Development and characterization of monoclonal antibodies targeting the major capsid protein (MCP) of scale drop disease virus (SDDV) - Yuting Fu; Jianfei Wan; Wenfeng Zhang; Yong Li; Jianguo He; Chuanfu Dong (Aquaculture, 2026)

3D-printed fish-scale dam-like structured photothermal evaporators based on thiol-ene click chemistry for solar-driven freshwater production and salt recovery - Lixuan Yang; Xiaoyu Fu; Zhihan Xu; Feiyue Zhou; Jingxing Gui; Yuting Xue; Yuxuan Ma; Dan Yu; Wei Wang (Journal of Cleaner Production, 2026)

The role and therapeutic potential of purinergic signaling pathway in metabolic syndrome-related atherosclerosis - Xiang Li; Chengxin Gong; Chengxiao Fu; Qing Xia; Yue Zhang; Yue Du; Yuting Sun; Hong Xu (Purinergic Signalling, 2026)

Decoding the gut-microbiota-muscle nexus: Multi-omics integration reveals mTOR driven flesh modulation in rice-fish co-cultured common carp (Cyprinus carpio) - Yinglin He; Bing Fu; Chang Fang; Niannian Zhang; Mengping Zheng; Yuting Yang; Shuping Zhang; Shijun Chen; Huirong Yang (Aquaculture, 2026)

Interaction mechanisms of short-chain fluorocarbon surfactants on metamorphic coal dust treatment: Insights from macroscopic experiments and molecular dynamics simulations - Zhenmin Luo; Kai Wang; Xuhan Ding; Yong Yang; Qingyun Fu; Tianting Wang; Yuting Wang; Tao Wang; Jingxiang Hao; Haipeng Jiang (Fuel, 2026)

Event‐Specific Meteorological Drivers Shape Diverse Water‐Use Efficiency Trajectories Under Drought Propagation - Feng Li; Qinchuan Xin; Julia K. Green; Chuixiang Yi; Armen R. Kemanian; Steven A. Kannenberg; Paul C. Stoy; Yuting Yang; Huimin Lei; Yujiu Xiong; Zheng Fu (Global Change Biology, 2026)
Drought propagation from meteorological to soil drought marks a critical phase in regulating vegetation water–carbon dynamics, yet the response trajectories of water‐use efficiency (WUE) during these events remain poorly understood. Here, combining global flux tower observations with simulations from Earth System Models (ESMs), we quantified the spatiotemporal patterns of drought propagation characteristics, identified WUE response trajectories for characteristic‐specific droughts, and investigated their dominant drivers. We found that 58% of soil droughts follow meteorological droughts. Most sites experience drought propagation events with increasing intensity, faster propagation, and shorter intervals. Among all identifiable trajectories, nonmonotonic patterns account for approximately 60%. WUE response trajectories generally follow continuous and nonmonotonic patterns, dominated by a rise‐then‐fall pattern. This pattern reflects a process in which vegetation functions regulated by stomatal behavior are initially stressed and then partially recover. Intra‐site variability is extremely pronounced, mainly driven by event‐specific thermal factors such as air temperature and net radiation. ESMs reproduce broad site‐level prevalence of nonmonotonic patterns, but show discrepancies in the relative importance of drivers due to the coupling of different land surface models. These findings challenge the notion of fixed vegetation functional responses and highlight the dynamic variability of response trajectories in relation to event‐specific characteristics, and provide concrete diagnostics to guide model improvements.

Fitness cost and molecular regulation analysis of thifluzamide resistance in Rhizoctonia solani AG-5 inciting maize banded leaf and sheath blight in Shanxi Province of China - Xiaojing Shi; Yuting Li; Naibo Yang; Shuhui Fu; Yanhua Xin; He Zhang (Pesticide Biochemistry and Physiology, 2025)

Global flood extent monitoring using SAR satellite and hydrological data: A multi-scale and multi-source approach - Yuting Zhu; Kei Yoshimura; Yingying Liu; Haohuan Fu (Journal of Hydrology, 2025)

Regulating electronegativity difference and piezoelectric strain of the Mo-S-Mo structure via introducing S vacancies for boosting piezo-photoelectric activity - Yanjiao Li; Yuting Ning; Xinping Fu; Yu Jiang; Lianfeng Wang; Jun Cui (Journal of Environmental Chemical Engineering, 2025)

Effects of high-moisture extrusion technology on structural properties, physicochemical properties and in-vitro starch digestibility of highland barley (Zangqing 3000) flour - Liping Fu; Yingting Zhao; Can Zhao; Yang Liu; Yixin Zheng; Yingying Yan; Qisen Xiang; Wenhui Zhang; Yuting Tian (Food Chemistry, 2025)

Injectable nanocomposite hydrogel with antibacterial/osteogenic dual functions for synergistic repair of infectious bone defects in hyperlipidemia microenvironment - Yongkai Wang; Yunhan Sun; Jiaming Song; Dongchen Fa; Yuting Qu; Jiayi Li; Xiao Fu; Li Ma (Chemical Engineering Journal, 2025)

Application of feruloyl esterase BpFae03105 and xylanase XynAS Co-enzymolysis to produce ferulic acid from wheat bran - Han Lichun; Zhong Xiufang; Fu Zhilei; Yan Jinlong; Xiao Lin; Zhu Yuting; Liu Xiaoyan; Rana Abdul Basit; Wang Jinpeng; Yin Dafeng; Fan Guangsen (Biocatalysis and Agricultural Biotechnology, 2025)

Publisher Correction to: Identification of a von Willebrand factor type A protein affecting both grain and flag leaf morphologies in wheat - Chunyun Zhou; Hongchun Xiong; Yong Jia; Huijun Guo; Meiyu Fu; Yongdun Xie; Linshu Zhao; Jiayu Gu; Huiyuan Li; Yuting Li; Peiyong Xin; Jinfang Chu; et al. (Science China Life Sciences, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

Meiotic cytokinesis defects in cultured Arabidopsis flowers induce diploid microspores - Huiqi Fu; Yuting Chen; Xueying Cui; Huishan He; Jingru Wang; Chong Wang; Ziming Ren; Bing Liu (Plant Reproduction, 2025)

Cover Image - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)

Detection and Genomic Characterisation of Scale Drop Disease Virus (SDDV) in Farmed Yellowfin Seabream ( Acanthopagrus latus ) in Southern China - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Scale drop disease virus (SDDV) is a distinct member of the genus Megalocytivirus within the family Iridoviridae , which was recently identified as a causative agent of yellowfin seabream Acanthopagrus latus ascitic diseases (YFSBAD). Here, a molecular surveillance of SDDV in pond‐cultured yellowfin seabream was conducted during 2021 to 2023 in Zhuhai, the most significant breeding region for this fish species in China. A total of 73 batches of naturally diseased yellowfin seabream samples were collected for SDDV detection. As a result, 31 samples were confirmed SDDV positive by conventional PCR detection, among which 9 additional SDDVs were isolated by using MFF‐1 cell line, and 4 isolates were further validated by monoclonal antibody‐based immunofluorescence assays. Multiple alignment and phylogenetic analysis revealed that these isolates shared the identical mcp sequences and were clustered within the same clade. Additionally, the complete genome sequence of a new SDDV isolate (SDDV‐ZH918/23) was determined and annotated. The result shows that SDDV‐ZH918/23 consists of 131,741 bp and encodes 143 putative open reading frames. The genome collinearity analysis demonstrated very high nucleotide similarity among all SDDV isolates distributed in China and other Asian countries. Unexpectedly, a 152 bp deletion mutant was also found in two SDDV isolates. Collectively, our study once again demonstrates that SDDV acts as an emerging etiological agent in farmed yellowfin seabream, and a partial deletion mutant of the SDDV genome was first recorded.

How to improve the environmental friendliness of the thermal power industry: A perspective on constructing cross-regional collaborative emission reduction mechanisms tailored to local conditions - Yuting Fu; Changhui Yang; Jennifer Shang; G.G. Hegde; Ling Wang (Sustainable Cities and Society, 2025)

Machine learning-guided anti-photoaging peptides from Chinese giant salamander skin: Efficient preparation and mechanistic insights - Yongjie Zhou; Huijuan Zhang; Chunyue Zhao; Zixin Fu; Yuting Wang; Sam K.C. Chang; Yan Zhang; Hui Hong; Yongkang Luo; Bo Li; Yuqing Tan (Food Chemistry, 2025)

Evaluating green total factor productivity in Chinese port listed companies based on biased technological change perspective - Yuting Zheng; Xiongjun Yuan; Dan Liu; Jingying Tang; Huishan Fu (Environment, Development and Sustainability, 2025)

A PVDF/PAN semi-interpenetrating network separator reinforced with Ce-ZIF67/LDH for suppressing zinc dendrites in aqueous zinc-ion batteries - Jinke Wang; Zheng Zhang; Yuting Shi; Ruili Li; Zepeng Fu; Meiyi Wang; Huashan Wang (Chemical Engineering Journal, 2025)

Chronic low-level exposure to Pb, Hg, and Cd mixture triggers brain premature aging in rat - Jie Xie; Lu Ouyang; Jiajun Li; Shuo Yang; Qi Li; Yue Li; Lingyu Yan; Yihong Fu; Qijun Li; Yuting Xia; Xinling Chen; Ziyang Fu; et al. (Toxicology, 2025)

Quality enhancement and metabolic mechanism of fermented sausages with Lactiplantibacillus plantarum and Companilactobacillus alimentarius - Fangrui Han; Qiancheng Wu; Shan Li; Yuting Luo; Zengkang Ding; Tong Luo; Jiesong Liang; Chenxiang Fu; Yingchen Wang; Zhongjie Yu (Food Bioscience, 2025)

Analysis of Morphological Characteristics of Male and Female Gymnocypris eckloni Herzenstein - Qiming Wang; Suxing Fu; Xiaoyi Chen; Yuting Duan; Luo Lei; Yawen Fan; Chaowei Zhou (Fishes, 2025)
Accurate sex identification is crucial for the artificial breeding of fish species, and identification based on phenotypic traits is the preferred method owing to its low cost and rapidity. This study aimed to investigate morphological differences between male and female Gymnocypris eckloni Herzenstein. A total of 166 G. eckloni individuals (83 males and 83 females) were included, and 20 morphological indicators, including head length, snout length, and body weight, were measured. Various analytical methods, such as correlation analysis, principal component analysis, discriminant analysis, and systematic cluster analysis, were used to compare the morphological characteristics of male and female G. eckloni. The result showed significant differences in morphological characteristics between male and female individuals (p ≤ 0.05). Principal component analysis revealed five main components that collectively contributed to 83.64% of the variance, primarily including body length, fork length, total length, and body weight, highlighting the significance of these components in sex differentiation. Subsequently, a mathematical model was constructed via discriminant analysis. This model demonstrated an accuracy of 79.5% and 73.5% in identifying male and female G. eckloni, respectively, with an overall accuracy of 76.50%. Furthermore, on analyzing the relationship between body length and body weight in G. eckloni, we found differences in growth patterns between sexes. In particular, female fish usually weighed more than male fish, which was consistent with the biological characteristics and energy distribution patterns of G. eckloni. These results suggest that sexual dimorphism in G. eckloni is primarily concentrated in body shape and head morphology, which provides a reliable basis for sex identification based on morphological differences.

Imidazole-ionic liquid-assisted solvent extraction mechanism-macro perspective and molecular aspect - Jinjian Hou; Wenjuan Wang; Zanli Fu; Yuting Hu; Zhongchi Wu; Xiaojin Wu; Jianan Hu; Haiming Yu; Gaobo Yu; Jiacheng Li (Journal of Hazardous Materials, 2025)

A nanozyme colorimetric sensor combined with cloud-based machine learning algorithm-assisted WeChat mini program for intelligent identification of Chinese green tea - Wanjun Long; Siyu Wang; Yangcheng Ling; Yuting Guan; Huiru Zhang; Hengye Chen; Wei Lan; Yuanbin She; Haiyan Fu (Food Research International, 2025)

Scale drop disease virus (SDDV) triggers ferroptosis both in mandarin fish (Siniperca chuatsi) and MFF-1 cells to facilitate virus infection via linking to transferrin receptor 1 (TfR1) - Jiaming Chen; Yuting Fu; Shuyi Chen; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Nanoparticle-assisted DES-catalyzed green and efficient synthesis of versatile hydrogels for degradable wearable sensors - Jun Hu; Jing Xu; Yuting Tian; Fangjian Shan; Jiangli Wei; Zixun Chen; Xiaoying Xin; Gaojian Chen; Guodong Fu (Chemical Engineering Journal, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

Multi-omics study reveals a light-dependent regulatory network of flavonoid biosynthesis in lettuce (Lactuca sativa L.) - Yuting Xiang; Shuxin Zheng; Hsihua Wang; Bang Chen; Rao Fu; Tao Huang; Li Zhang; Bo Song; Yuejian Li; Qichang Yang; Xiao Yang; Yang Zhang (Science China Life Sciences, 2025)

Identifying the ideal habitats for authentic herbs to cope with climate warming: a case study of Forsythia suspensa - Zikang Lu; Yinfeng Yu; Yuting Liu; Xiangrui Fu; Xuhong Duan; Errong Yu; Xueqiang Guo; Jiankun Yan; Kaiyan Zheng; Xian Gu; Donglai Ma (Environmental Monitoring and Assessment, 2025)

Digitally interactive smart textiles in football prepared by an outstanding viscose-based flexible strain sensor - Shidong Ma; Yuting Wu; Jian Tang; Jiayi Fu; Han Liu; Yumin Zhang; Jinyu Ma; Zhijuan Pan; Tao Yan (Chemical Engineering Journal, 2025)

Experimental and molecular dynamics analysis on the mechanism of -pSO3H, -OSO3H and heavy alkyl functional groups in affecting wetting and agglomeration behaviour of coal particles during dust suppression - Xuhan Ding; Qingyun Fu; Kai Wang; Qian Xu; Tianting Wang; Zhenmin Luo; Yuting Wang; Minjun Ma; Yongzhe Zhang; Tao Wang; Jiuzhu Wang (Journal of Environmental Chemical Engineering, 2025)

Control of sedimentary and diagenetic processes on the reservoir heterogeneity: A case study of the cretaceous carbonate reservoir in an onshore oilfield, Abu Dhabi - Yuting Peng; Yingxiao Fu; Hangyu Liu; Kaibo Shi; Bo Liu; Rubing Han; Xili Deng (Journal of African Earth Sciences, 2025)

RalB promotes lymph node metastasis in tongue squamous cell carcinoma - Yuman Zhang; Jiali Yang; Yi Gong; Zhihan Liu; Yanguang Yang; Xiaoyong Song; Yuting Gao; Yajun Xiong; Dan Wang; Kai Fu; Lifeng Jia; Xinli Shi (Genes & Genomics, 2025)

Advances and applications in single-cell and spatial genomics - Jingjing Wang; Fang Ye; Haoxi Chai; Yujia Jiang; Teng Wang; Xia Ran; Qimin Xia; Ziye Xu; Yuting Fu; Guodong Zhang; Hanyu Wu; Guoji Guo; et al. (Science China Life Sciences, 2025)

Hesperidin alleviates endothelial cell inflammation and apoptosis of Kawasaki disease through inhibiting the TLR4/IĸBα/NF-ĸB pathway - Yuting Guan; Jinghua Ruan; Pingping Tan; Songwei Qian; Size Zhou; Ao Zhang; Yuchong Fu; Shuhui Zhao; Yuqing Ran; Xing Feng; Yijia Wang; Xinlei Wu; et al. (Chemico-Biological Interactions, 2025)

Unraveling the edaphic factors driving organic material decay: Insights from long-term manure application studies - Yuting Fu; Sabine Ravnskov; Marcos Paradelo; Lis W. de Jonge; Emmanuel Arthur (Soil Biology and Biochemistry, 2025)

Preparation and characterization of lauric acid-rich wax oleogel chocolates: Insights into crystallization behavior, storage stability, and bloom resistance - Yuting Fu; Yu Chen; Pengyan Li; Chuan Li; Zhiguo Wang; Jun Cao (Food Research International, 2025)

The Co‐Infection of ISKNV ‐ II and RGNNV Resulting in Mass Mortality of Juvenile Asian Seabass ( Lates calcarifer ), Zhuhai, Southern China - Qianqian Sun; Shan Ding; Xiangrong Liu; Wenfeng Zhang; Fangzhao Yu; Yuting Fu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Infectious spleen and kidney necrosis virus (ISKNV) and nervous necrosis virus (NNV) are two common and important causative agents in marine‐cultured fish. However, high viral loads of both ISKNV and NNV in the same clinical case is unusual. In this study, a mass mortality event of Asian seabass Lates calcarifer juveniles occurred in Zhuhai, the main Asian seabass cultured area in mainland China. The fish samples were pooled for pathogen identification and both high viral loads of ISKNV and NNV were detected by real‐time microfluidic quantitative PCR and conventional PCR. Immunohistochemistry and immunofluorescence showed that strong ISKNV signals were detected in spleen and liver, while strong NNV signals were detected in brain and eye. The tissue homogenates were inoculated into MFF‐1 cell and SSN‐1 cell, respectively. After several viral passages, both individual ISKNV and NNV were purely isolated from each other, and designated as ASB‐ISKNV‐23 and ASB‐NNV‐23, respectively. The whole genome sequences of ASB‐ISKNV‐23 and ASB‐NNV‐23 were determined and annotated. The result showed that ASB‐ISKNV‐23 and ASB‐NNV‐23 are composed of 112,236 bp and 4441 bp, respectively. Phylogeny analysis showed that ASB‐ISKNV‐23 belongs to ISKNV‐II sub‐genotype and ASB‐NNV‐23 belongs to RGNNV genotype. Collectedly, coinfection of ISKNV‐II and RGNNV were firstly documented in mass mortality of Asian seabass in mainland China. Importantly, both individual ISKNV‐II and RGNNV were purely isolated using two different permissive cell lines. Our study provides useful information for better understanding the complex pathogenesis regarding the coinfection with ISKNV and NNV in farmed fish.

A nationwide probabilistic risk assessment and a new insight into source-specific risk apportionment of antibiotics in eight typical river basins in China: Human health risk and ecological risk - Cong Men; Haoquan Jiang; Yuting Ma; Hengjiang Cai; Han Fu; Zifu Li (Journal of Hazardous Materials, 2025)

Deep eutectic solvent-mediated sunlight polymerization for rapid fabrication of degradable hydrogel-based wearable sensors - Jun Hu; Fangjian Shan; Yuting Tian; Jiangli Wei; Zixun Chen; Weining Liu; Gaojian Chen; Guodong Fu (Chemical Engineering Journal, 2025)

Vocalization-induced middle ear muscle reflex and auditory fovea do not contribute to the unimpaired auditory sensitivity after intense noise exposure in the CF-FM bat, Hipposideros pratti - Zhongdan Cui; Jianwen Zou; Yuting Zhou; Yuntu Cao; Haonan Song; Haoyue Xu; Jing Wu; Baoling Jin; Lijian Yang; Ya Jia; Qicai Chen; Ziying Fu (Journal of Comparative Physiology A, 2025)

Multifunctional biomass-based solar evaporator with enhanced sterilization performance for solar-driven clean water evaporation - Hongbin Cao; Dong Li; Jingjing Fu; Yuxin Yang; Yanyan Zheng; Yuting Que; Xiu He; Haiyan Wang; Jun Liu; Huang Zhou (Desalination, 2024)

Physical, Chemical, Biological, and Synergistic Technologies for Remediation of Pesticide-Contaminated Soil - Qian Li; Dongdong Wen; Caidie Qin; Yuting Qian; Rongbing Fu; Sijie Lin (Reviews of Environmental Contamination and Toxicology, 2024)

Hydroxypropyl methycellulose-galactomannan binary complexes achieving 55 wt% curcumin loading capacity: Mechanism and bioactivity - Haifeng Wang; Chenhui Wang; Jiang Mou; Yuting Wang; David W. Everett; Wenle He; Teng Li; Yuying Fu (Food Hydrocolloids, 2024)

Synthesis of highly transparent and fast-responding photochromic coating by template method with space-limited domains - Yuting Tian; Weining Liu; Jun Hu; Zhiwei Li; Xiaoying Xin; Guodong Fu (Chemical Engineering Journal, 2024)

Simultaneous solar-driven interfacial evaporation and phenol degradation using three-dimensional MoS2-melamine foam - Yanli Fu; Litao Xie; Jing Li; Xinge Li; Mengshi Su; Yuting Liu; Liangguo Yan (Chemical Engineering Journal, 2024)

Decoding the intestinal response to heat stress in Gymnocypris eckloni: Insights from a thorough analysis of microbiome and transcriptome - Chaowei Zhou; Yuting Duan; Junting Li; Suxing Fu; Shuhao Bai; Yutong Zhuang; Hejiao Li; Yinhua Zhou; Jian Shen; Rongpan Zhou; Fan Yang; Zhichao Liu; et al. (Aquaculture, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Identification of a von Willebrand factor type A protein affecting both grain and flag leaf morphologies in wheat - Chunyun Zhou; Hongchun Xiong; Yong Jia; Huijun Guo; Meiyu Fu; Yongdun Xie; Linshu Zhao; Jiayu Gu; Huiyuan Li; Yuting Li; Peiyong Xin; Jinfang Chu; et al. (Science China Life Sciences, 2024)

Study on the spatial and temporal evolutionary characteristics of ozone concentration and the impact of human activities in China in 2019 - Yongchun Wang; Wang Zhang; Yu’an Liu; Yazhu Wang; Yuting Fu; Zhaohui Feng; Lingqing Wang (Acta Geochimica, 2024)

A colorimetric sensor based on 4-MPBA Au@AgNPs for accurately identification of EnshiYulu tea grade - Yuting Guan; Siyu Wang; Guanghua Lei; Zikang Hu; Hengye Chen; Huiwen Gu; Xiaoli Yin; Yuanbin She; Wanjun Long; Haiyan Fu (Food Chemistry, 2024)

Dietary exposure to sulfamethazine, nanoplastics and their binary mixture disrupts the spermatogenesis of marine medaka (Oryzias melastigma) - Yuting Zhang; Ruanni Chen; Zhiqiang Chen; Xiaoyu Fu; Ziyi Wu; Jinwan Chen; Lingtian Xie; Humin Zong; Jingli Mu (Acta Oceanologica Sinica, 2024)

Integrated transcriptome and 16S rDNA analyses reveal that acute heat stress induces intestinal damage in Gymnocypris eckloni - Yuting Duan; Hejiao Li; Junting Li; Shuhao Bai; Suxing Fu; Yinhua Zhou; Shidong Liu; Rundong Li; Haiping Liu; Chaowei Zhou; Luo Lei (Frontiers in Marine Science, 2024)
Gymnocypris eckloni ( G. eckloni ), a cold-water economic fish, is widely cultivated in southwestern China. The increase in extreme summer weather conditions owing to global warming can significantly affect their survival and health. The fish intestine and its microbiota are closely associated with fish feeding and growth, nutritional metabolism, and immune defense. However, the mechanisms underlying the changes in the G. eckloni intestine and its microbiota under acute heat stress remain unknown. In this study, we investigated the effects of acute heat stress on the G. eckloni intestine employing histology, plasma biochemical indices, transcriptomics, and 16S rDNA sequencing. Histological analysis showed that acute heat stress induced significant morphological damage to the intestine, with microvilli detachment and mitochondrial abnormalities in the ultrastructure. Biochemical indicators associated with stress (reactive oxygen species and catalase), inflammation (interleukin-1β and tumor necrosis factor-α), and intestinal permeability (diamine oxidase and lipopolysaccharide) were significantly elevated after acute heat stress, indicating an intestinal inflammatory response and disruption of barrier function. Many DEGs were mined by transcriptomic analysis, with tfrc, pfkp, egln1 enriched in the HlF-1 signaling pathway, hsp70, hsp90aa1 and hspa4 enriched in the Antigen processing and presentation pathway, pmm1 , pfkfb3 and hk1 enriched in the Fructose and mannose metabolism patyway. The HIF-1 signaling pathway is a crucial regulatory pathway during acute heat stress in the G. eckloni intestine, while significant downregulation of genes associated with adaptive immunity ( mica , hla-dpa1 , hla-dpb1 , and hla-dqb2 ) suggested impaired immune function. Additionally, the composition of the intestinal microbiota was dominated by Aeromonas , Citrobacter , and Acinetobacter in the control group; but there was a significant decrease in the abundance of Citrobacter and Acinetobacter , and a significantly increased in Shewanella and Hafnia-Obesumbacterium after acute heat stress. Correlation analyses revealed that changes in the abundance of Hafnia-Obesumbacterium , Buttiauxella , and Pseudomonas were closely associated with changes in gene expression associated with stress, inflammation, and immunity. These results comprehensively demonstrate the adaptive mechanisms of the G. eckloni intestine in response to acutely high temperatures and provide a theoretical basis for the future advancement of artificial culture of cold-water fish.

The role of Pm-miR-184-3p in regulating the immune response in the pearl oyster Pinctada fucata martensii - Shirong Fu; Yuting Zhang; Yu Jiao; Qingheng Wang; Yuewen Deng; Xiaodong Du (Fish & Shellfish Immunology, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Exposure to atrazine stimulates progesterone secretion and induces oxidative stress, inflammation, and apoptosis in the ovary of pseudopregnant rats - Jie Zhao; Guangjun Huang; Yuting Fu; Zhangbo Lou; Hao Yu; Wei Wang; Dagan Mao (Chemosphere, 2024)

A comprehensive review of biodetoxification of trichothecenes: Mechanisms, limitations and novel strategies - Yue Qiu; Jiaping Yan; Aodong Yue; Zhongchao Lu; Jianzhuang Tan; Hong Guo; Yuting Ding; Fei Lyu; Yan Fu (Food Research International, 2024)

Hierarchical Cu dendrites@ CuO multifunctional nanowire mesh for solar-thermal clean water production - Huang Zhou; Hongbin Cao; Yuting Que; Yifei Chen; Jingjing Fu; Haiyan Wang; Yanyan Zheng; Xiu He; Yuxin Yang; Jun Liu (Desalination, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Regional feed-in tariff mechanism for photovoltaic power generation in China considering tradable green certificate revenue - Yuting Fu; Changhui Yang; Liangao Zhang; Ling Wang; Kai Jiang (Journal of Cleaner Production, 2024)

Two-Omics Probe on the Potential of Pseudomonas sp. GDMCC 1.1703 Under Phenol Stress - Hongfei Zhu; Jiashuai Yu; Yuting Fu; Xiaoshuang Mao; Haimei Yang (Current Microbiology, 2024)

Discovery and identification of a novel canine coronavirus causing a diarrhea outbreak in Vulpes - Yuting Liu; Yao Deng; Sheng Niu; Na Zhu; Jingdong Song; Xiaoshuang Zhang; Weiting Su; Wenhui Nie; Roujian Lu; David M. Irwin; George Fu Gao; Wenling Wang; et al. (Science Bulletin, 2023)

Genome-wide characterization of two homeobox families identifies key genes associated with grain-related traits in wheat - Yuting Li; Hongchun Xiong; Huijun Guo; Linshu Zhao; Yongdun Xie; Jiayu Gu; Shirong Zhao; Yuping Ding; Huiyuan Li; Chunyun Zhou; Meiyu Fu; Qingguo Wang; et al. (Plant Science, 2023)

Carbon emissions induced by land use and land cover change amid rapid urbanization in Chengdu-Chongqing economic circle, China: efficiency, transfer and process - Zhonglin Tang; Shan Ma; Min Fu; Yuting Wang; Jingyue Xue; Yuanfu Yin; Yang Xiao (Environment, Development and Sustainability, 2023)

Using association mapping and local interval haplotype association analysis to improve the cotton drought stress response - Wenju Gao; Qin Chen; Jincheng Fu; Hui Jiang; Fenglei Sun; Shiwei Geng; Yuxiang Wang; Jieyin Zhao; Yuting Xie; Man Zhou; Yanying Qu; Quanjia Chen (Plant Science, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

Classification of Chinese traditional cereal vinegars and antioxidant property predication by fluorescence spectroscopy - Wanjun Long; Guanghua Lei; Yuting Guan; Hengye Chen; Zikang Hu; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

The role of semiannual cycle in modulating seasonality changes of surface air temperature over China and its mechanism - Qimin Deng; Yuting Wang; Xin Tan; Zuntao Fu (Climate Dynamics, 2023)

Laboratory tidal microcosm deciphers responses of sediment archaeal and bacterial communities to microplastic exposure - Chang Fang; Yinglin He; Yuting Yang; Bing Fu; Sentao Pan; Fang Jiao; Jun Wang; Huirong Yang (Journal of Hazardous Materials, 2023)

Effects of garlic peptides on rheology, moisture, microstructure, gluten distribution, and baking properties of dough - Xiaorong Liu; Qianran Xie; Dezheng Liu; Yuting Zhang; Shensheng Xiao; Wenping Ding; Yang Fu; Xuedong Wang (Journal of Cereal Science, 2023)

Oxidative pretreatment of refractory gold ore using persulfate under ultrasound for efficient leaching of gold by a novel eco-friendly lixiviant: Demonstration of the effect of particle size and economic benefits - Qihao Gui; Likang Fu; Yuting Hu; Haokai Di; Ming Liang; Shixing Wang; Libo Zhang; Enhua Dong (Hydrometallurgy, 2023)

A novel AD theranostic platform with NIR-II laser controlled drug release and real-time monitoring of therapeutic outcomes - Zhili Qiu; Guojun Cao; Shanrong Lv; Dehong Yu; Jingjing Fu; Hanrong Yan; Yuting Li; Peng Zhou; Xiunan Wu; Zhao Liu; Fenglei Gao (Chemical Engineering Journal, 2023)

Fine mapping and genetic analysis identified a C2H2-type zinc finger as a candidate gene for heading date regulation in wheat - Yuting Li; Hongchun Xiong; Huijun Guo; Chunyun Zhou; Meiyu Fu; Yongdun Xie; Linshu Zhao; Jiayu Gu; Shirong Zhao; Yuping Ding; Chaojie Wang; Ahsan Irshad; et al. (Theoretical and Applied Genetics, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Effectively protecting Asian seabass Lates calcarifer from ISKNV-I, ISKNV-II, RSIV-II and SDDV by an inactivated ISKNV-I and SDDV bivalent vaccine - Yuting Fu; Yong Li; Wenfeng Zhang; Weixuan Fu; Wangdong Li; Zhiming Zhu; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Effects of selected Bacillus strains on the biogenic amines, bioactive ingredients and antioxidant capacity of shuidouchi - Yuting Chen; Wenshan Luo; Manqin Fu; Yuanshan Yu; Jijun Wu; Yujuan Xu; Lu Li (International Journal of Food Microbiology, 2023)

Failure mechanism and movement process of three loess landslides due to freeze-thaw cycle in the Fangtai village, Yongjing County, Chinese Loess Plateau - Jiaxu Kong; Jianqi Zhuang; Jianbing Peng; Penghui Ma; Jiewei Zhan; Jiaqi Mu; Jie Wang; Dan Zhang; Jia Zheng; Yuting Fu; Shibao Wang; Chenhui Du (Engineering Geology, 2023)

3D-printed GA/PPy aerogel biocathode enables efficient methane production in microbial electrosynthesis - Yuting He; Jun Li; Liang Zhang; Xun Zhu; Yuan Pang; Qian Fu; Qiang Liao (Chemical Engineering Journal, 2023)

A novel pathogenic deletion in ISPD causes Walker-Warburg syndrome in a Chinese family - Yuting Shi; Yimei Fu; Zhouteng Tao; Wenjing Yong; Huirong Peng; Wenyang Jian; Gang Chen; Manhui Guo; Yanhua Zhao; Ruojin Yao; Dewei Guo (Genes & Genomics, 2023)

Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue - Wenfeng Zhang; Hengwei Deng; Yuting Fu; Weixuan Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Journal of Fish Diseases, 2023)
Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.

Effects of microplastics on nitrogen and phosphorus cycles and microbial communities in sediments - Maoyun Yin; Bin Yan; Huan Wang; Yan Wu; Xiang Wang; Jueqiao Wang; Zhihao Zhu; Xixi Yan; Yuting Liu; Meijun Liu; Chuan Fu (Environmental Pollution, 2023)

Gold extraction using alternatives to cyanide: Ultrasonic reinforcement and its leaching kinetics - Qihao Gui; Likang Fu; Yuting Hu; Haokai Di; Ming Liang; Shixing Wang; Libo Zhang (Minerals Engineering, 2023)

Estimation of hourly actual evapotranspiration over the Tibetan Plateau from multi-source data - Xian Wang; Lei Zhong; Yaoming Ma; Yunfei Fu; Cunbo Han; Peizhen Li; Zixin Wang; Yuting Qi (Atmospheric Research, 2023)

Insight into biofilm-forming patterns: biofilm-forming conditions and dynamic changes in extracellular polymer substances - Yue Wang; Meng Fu; Bowen Wu; Mingyan Huang; Tian Ma; Hailian Zang; Hanyi Jiang; Yuting Zhang; Chunyan Li (Environmental Science and Pollution Research, 2022)

BCI system with lower-limb robot improves rehabilitation in spinal cord injury patients through short-term training: a pilot study - Zhengzhe Cui; Yongqiang Li; Sisi Huang; Xixi Wu; Xiangxiang Fu; Fei Liu; Xiaojiao Wan; Xue Wang; Yuting Zhang; Huaide Qiu; Fang Chen; Peijin Yang; et al. (Cognitive Neurodynamics, 2022)

The melanocortin-4 receptor (MC4R) gene in the gibel carp Carassius auratus gibelio: cloning, tissue distribution, and fasting effects - Yan Zhou; Yan Li; Luo Lei; Xingxing Deng; Yuting Duan; Suxing Fu; Jingsen Zhang; Dengyue Yuan; Chaowei Zhou; Wenping He (Aquaculture International, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

The activity, segmentation, and evolution characteristics of large-scale landslides along the Anninghe active fault zone, Southwest China - Hongfu Zhou; Fei Ye; Wenxi Fu; Yuting Wei; Yadong Qin; Wenqing Tang; Tian Fang (Bulletin of Engineering Geology and the Environment, 2022)

Exploitation of the antifungal and antibiofilm activities of plumbagin against Cryptococcus neoformans - Weidong Qian; Wenjing Wang; Jianing Zhang; Yuting Fu; Qiming Liu; Xinchen Li; Ting Wang; Qian Zhang (Biofouling, 2022)

Numerical and Experimental Analysis of Transient Flow Field and Pressure Pulsations of an Axial-Flow Pump Considering the Pump–Pipeline Interaction - Fan Yang; Zhongbin Li; Jianguo Fu; Yuting Lv; Qingwei Ji; Hongfu Jian (Journal of Marine Science and Engineering, 2022)
The internal flow in a vertical axial-flow pump is a complex unsteady three-dimensional viscous flow. An unstable flow often produces complex flow phenomena such as flow separation, vortices, and secondary reflux, which reduces the operating efficiency of the pump and can endanger safety and stability. In this paper, computational fluid dynamics is used to calculate the flow characteristics in an axial-flow pump using the shear stress transport and curvature correction (SST-CC) model for turbulence modified to account for the rotational curvature. Furthermore, the dependability of the numerical results was confirmed by a test with an actual model of a pump. The transient deviation angle at the impeller inlet of the pump, the stream field attributes in various spanwise parts of the impeller and guide vane, and the velocity distributions at the impeller inlet and outlet were analyzed. The omega method was utilized to recognize the vortex structure inside the guide vane. Moreover, the development of the transient vortex structure inside the guide vane was studied. As the flow rate increased, the scale and turbulent kinetic energy of the vortex structure gradually decreased. The time-domain graph for the impeller inlet is clearly periodic, with three peaks and three troughs in an impeller rotational period. The dominant frequency in the spectrum at each monitoring point was basically the blade frequency, and the secondary dominant frequency was twice the blade frequency.

Effect of paeonol against bacterial growth, biofilm formation and dispersal of Staphylococcus aureus and Listeria monocytogenes in vitro - Qiao Zeng; Yuting Fu; Min Yang; Ting Wang; Ying Wang; Shenghua Lv; Weidong Qian (Biofouling, 2022)

Association of lncRNA PRNCR1 polymorphisms with cancer susceptibility: a meta-analysis of the current literature - Peng Du; Guoyong Li; Jisheng Zhu; Yuting Luo; Nantao Fu; Yong Li (Journal of Genetics, 2021)

In vitro anti-biofilm efficacy of sanguinarine against carbapenem-resistant Serratia marcescens - Yuting Fu; Wanting Liu; Miao Liu; Jianing Zhang; Min Yang; Ting Wang; Weidong Qian (Biofouling, 2021)

Equivalent effect of extracellular proteins and polysaccharides on biofilm formation by clinical isolates of Staphylococcus lugdunensis - Weidong Qian; Wenjing Wang; Jianing Zhang; Miao Liu; Yuting Fu; Mingming Li; Jing Jin; Wei Cui; Chengbin Wang (Biofouling, 2021)

Vertical bearing characteristics of rock-socketed pile in a synthetic soft rock - Bin Huang; Yuting Zhang; Bu Lv; Zhijun Yang; Xudong Fu; Benjiao Zhang (European Journal of Environmental and Civil Engineering, 2021)

Effects of Fluorine on Intestinal Structural Integrity and Microbiota Composition of Common Carp - Huiyuan Yu; Yue Zhang; Peijun Zhang; Xinchi Shang; Yuting Lu; Yunhe Fu; Yuehong Li (Biological Trace Element Research, 2020)

A review of microplastics in the aquatic environmental: distribution, transport, ecotoxicology, and toxicological mechanisms - Jia Du; Shaodan Xu; Qingwei Zhou; Huanxuan Li; Li Fu; Junhong Tang; Yangyang Wang; Xu Peng; Yuting Xu; Xinpeng Du (Environmental Science and Pollution Research, 2020)

Stress associated protein 1 regulates the development of glandular trichomes in Artemisia annua - Yuting Wang; Xueqing Fu; Lihui Xie; Wei Qin; Ling Li; Xiaofen Sun; Shihai Xing; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

A Multiobjective Stochastic Programming Model for Hydropower Hedging Operations under Inexact Information - Bin Xu; Ping-an Zhong; Yenan Wu; Fangming Fu; Yuting Chen; Yunfa Zhao (Water Resources Management, 2017)

ALFF Value in Right Parahippocampal Gyrus Acts as a Potential Marker Monitoring Amyotrophic Lateral Sclerosis Progression: a Neuropsychological, Voxel-Based Morphometry, and Resting-State Functional MRI Study - Wenjia Zhu; Xiaoling Fu; Fang Cui; Fei Yang; Yuting Ren; Xiaoyun Zhang; Xiaolan Zhang; Zhaohui Chen; Li Ling; Xusheng Huang (Journal of Molecular Neuroscience, 2015)

Rapid Evolution of Simple Sequence Repeat Induced by Allopolyploidization - Zongxiang Tang; Shulan Fu; Zhenglong Ren; Yuting Zou (Journal of Molecular Evolution, 2009)